The feminist critique of architecture: Learning from Denise Scott Brown and Frances Bradshaw - Caluwé,Goedele De (2016)
Against the backdrop op Betty Friedan's account of women's experience in suburban America, a feminist critique of architecture started to take form in the seventies and eighties. The main divide between what is called equality feminism and difference feminism, is very clearly reflected in the writings of feminists and architects who were active in the field at the time. For this paper I will focus specifically on Denise Scott Brown and Frances Bradshaw. I will look at how different feminisms were translated into very different feminist critiques of architecture. After that I will look at parallels and differences between both women's writings, in order to establish how their work is still relevant today, when seen from a post-structuralist perspective.